Vpliv nadzorovane podhladitve na zdravljenje bolnikov po srčnem zastoju - Kavčič, Marko (Medicinski razgledi, 2006)
Cardiac arrest is the most common cause of sudden natural death. Ischemia during cardiac arrest and reperfusion damage after resuscitation are often thesource prevention of permanent neurological impairment in survivors. Induced hypothernia opened the possibility of effective causal prevention of neurological damage. Induced hypothermia has been used as a standard treatmentat the Center for Intesive Internal Medicine (CIIM) since year 2004. We included patients who were treated at the CIIM in the period from 1 January2001 to 29 April 2005 following primary cardiac arrest. All enrolled patients fulfilled the criteria for treatment with induced hypothermia. The test group consisted of all patients treated after 1 January 2004, when induced hypothermia was adopted as the standard treatment method and the control group included all other patients from the observed time period. Survival, rate of neurological recovery and long-term neurological outcomes were compared, as well as the rate of complications. The final analysis included 123 patients, of whom 49 had been treated with hypothermia and 74 were control subjects. The two patient groups were comparable in terms of their basic characteristics and treatment (with the exception of controlled hypothermia). After half a year, 51% of patients who had been treated with hypothermia and 30% of those from the control group had a favorable neurological outcome (p=0.0223). In this period, 40.8% of patients treated with hypothermia and 60% of those from the control group died (p=0.0434). Noneof the treatment complications showed a statistically significant deviations in incidence between the two groups. 53% of patients treated with hypothermia and 79% of the control subjects were responsive in first three days (p = 0.03), while meaningful response was possible in 23% of patients treated with hypothermia and 72% of control subjects (p=0.001). (Abstract truncated at 2000 characters)
Keywords: srčne bolezni; srčni zastoj; podhladitev; therapy; zdravljenje